Key programmatic and policy considerations for introducing multipurpose prevention (MPT) methods: reflections from healthcare providers and key stakeholders in South Africa - Kutywayo, Alison; Mataboge, Paballo; Mthimkhulu, Nqaba; Martin, Catherine E.; Muhwava, Lorrein S.; Mazibuko, Mbali; Makalela, Nthabiseng; Kwatsha, Khanyiswa; Butler, Vusile; Mullick, Saiqa (Frontiers in Reproductive Health, 2024)
Introduction Multipurpose prevention technologies (MPTs) simultaneously prevent HIV, other sexually transmitted infections, and/or unintended pregnancy. Key gatekeepers, [healthcare providers (HCPs) and key stakeholders] require proactive engagement before product implementation. This manuscript identifies HCP demand creation strategies, key stakeholder considerations for the adoption of MPTs in South Africa. Methods Formative research was conducted in three districts in three South African provinces (July to November 2022). Nurses initiating oral PrEP at facility and mobile study sites participated in 4-hour participatory workshops, exploring HIV prevention, including MPTs, demand creation strategies, and preferred MPTs training packages. Activities were observed, transcribed, and thematically analysed. Five online in-depth interviews (IDIs) with Key informants (KIs) (National/district programme implementers and technical leads) and one in person, exploring key programmatic and policy considerations for MPT adoption. IDIs were approximately 40 min long, audio recorded, transcribed, and thematically analysed. Results Twenty-one Professional Nurses completed workshops: 19 female. Six IDIs were conducted with 4 Facility Managers, 1 NDoH representative and 1 DoH Provincial Deputy Director. All participants were females, aged 30–60+ years with >10 years' in SRH/HIV policy/advocacy/research. Community conversations and information at the clinic were the best MPT demand creation methods among HCPs. KIs identified five considerations for future MPT implementation: HCP training; demand creation and messaging; existing PrEP policy amendments; preparing users for additional choice; and sustaining MPT provision. Conclusion Contraceptive implant and oral PrEP implementation lessons learned should be proactively considered when preparing for MPT introduction. HCP training and demand creation are of particular importance before MPT introduction.